ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK - Putri, Phany Ineke (Semarang State University, 2013)
The purpose of this study was to analyze the influence of population, income per capita, inflation and the number of Trade Permit toward billboard tax revenue in Purbalingga. The results of this study is expected to provide benefit and input to the Local Government of Purbalingga, especially Departement of management of financial income and regional asset. Analysis tool used is multiple linear regression (Multiple Linear Regression Method) by the method of least squares Ordinary Least Square (OLS). Jointly test results showed that overall independent variables (population, income per capita, inflation, and the number of trade permit) together to show their effects on the billboard tax revenue. Adjusted R-Squared value of 0,951, which means 95,1 percent of the four independent variables. While the remaining 4,9 percent is explained by other causes outside the model. The results showed that the per capita income variable and the number of trade permit have a significant positive effect, the inflation variable has a significant negative effect, whereas a number of population variable have a positive effect which is not significant at Î± = 5 percent of tax revenue in Purbalingga billboard.Â Tujuan dari penelitian ini adalah untuk menganalisis pengaruh jumlah penduduk, pendapatan per kapita, inflasi dan jumlah surat ijin usaha perdagangan (SIUP) terhadap penerimaan pajak reklame di Kabupaten Purbalingga. Manfaat penelitian ini diharapkan menjadi bahan masukan Pemerintah Kabupaten Purbalingga khususnya Dinas Pengelolaan, Pendapatan, Keuangan dan Aset Daerah. Teknik analisis yang digunakan adalah regresi berganda dengan metode Ordinary Least Square (OLS). Hasil penelitian menunjukkan ada pengaruh secara bersama-sama variabel jumlah penduduk, pendapatan per kapita, inflasi dan jumlah surat ijin usaha perdagangan terhadap penerimaan pajak reklame. Koefisien determinasi 95,1% dapat dijelaskan oleh variabel independen terhadap variabel dependen, dan sisanya dijelaskan oleh variabel lain diluar model yang diteliti. Pendapatan per kapita dan jumlah surat ijin usaha berpengaruh signifikan positif, sedangkan inflasi berpengaruh signifikan negatif dan jumlah penduduk tidak berpengaruh terhadap penerimaan pajak reklame.